Clinical studies in medical biochemistry - Glew, Robert H.; Rosenthal, Miriam D. (Oxford University Press, 2007)
This text uses a case-study approach to present the core principles of biochemistry and molecular biology in the context of human disease to students who will be involved in patient care. The 33 cases are carefully selected to cover key concepts and common diseases. Each chapter provides a specific patient report that includes the relevant history, pertinent clinical laboratory data, physical findings, and subsequent diagnosis. This is followed by a comprehensive discussion of the normal biochemical processes and reactions pertaining to the case, along with the pathophysiological mechanisms of.